A review on the laser-assisted flow deposition method: growth of ZnO micro and nanostructures - Rodrigues, Joana (2019)
Zinc oxide (ZnO) is a widely versatile semiconductor with major importance from the technological point of view, presenting the advantage to be grown by a large number of techniques and with one of the richest varieties of morphologies. Due to the special interest of this semiconductor, several methods have been developed to control the production of its nanostructures. Herein, we report the development of a vapour-based method, designated by laser-assisted flow deposition (LAFD), able of producing ZnO micro and nanocrystals with different morphologies, with a high crystalline and optical quality. This new process allows high yield of ZnO production, showing great prospects for scalable applications. In the present work, we review in detail the main growth parameters and their relationship with the produced morphologies, in addition to their influence in the structural and optical properties. Furthermore, an assessment of the possible growth mechanisms that may be involved in this new method is reported. Some potential applications of the ZnO structures produced by LAFD were also evaluated, with focus on the photocatalysis and photovoltaic fields. Additionally, the possibility of synthesizing ZnO composite nanostructures, as well as the growth of other metal oxides using this technique was explored.